2022
DOI: 10.3390/plants11243487
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Aureimonas altamirensis C2P003—A Specific Member of the Microbiome of Fraxinus excelsior Trees Tolerant to Ash Dieback

Abstract: Some European ash trees show tolerance towards dieback caused by the invasive pathogen Hymenoscyphus fraxineus. The microbiome of these trees harbours a range of specific bacterial groups. One of these groups belonging to the species Aureimonas altamirensis was studied in detail by genome analysis and a plant inoculation trial. The strain group was shown to be phylogenetically distinct from clinical isolates by 16S rRNA analysis and phylogenomics. Genome analysis of a representative strain C2P003 resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…However, the obtainment of a single A. altamirensis strain can be associated with the absence of a specific isolation procedure, as the isolation of this bacterium is performed using several nonselective media [10,13,16,19]. The whole-genome analysis (Supplementary Table S1) of the strain isolated in this work (strain AAI) showed a genome of 4.1 Mb with a GC percentage of 64.99%, 4041 coding DNA sequences (CDS), and 3 16S rDNA, 1 23S rRNA, and 47 tRNA demonstrating characteristics comparable to other isolates of the same species [17]. The dendrogram tree (Figure 2) showed a high similarity between AAI and two A. altamirensis strains isolated from the oxygen minimum zone (OMZ) water column and pleural fluid showing the absence of similarity of AAI with isolates from a specific matrix.…”
Section: A Altamirensis Isolation Identification and Characterizationmentioning
confidence: 65%
See 3 more Smart Citations
“…However, the obtainment of a single A. altamirensis strain can be associated with the absence of a specific isolation procedure, as the isolation of this bacterium is performed using several nonselective media [10,13,16,19]. The whole-genome analysis (Supplementary Table S1) of the strain isolated in this work (strain AAI) showed a genome of 4.1 Mb with a GC percentage of 64.99%, 4041 coding DNA sequences (CDS), and 3 16S rDNA, 1 23S rRNA, and 47 tRNA demonstrating characteristics comparable to other isolates of the same species [17]. The dendrogram tree (Figure 2) showed a high similarity between AAI and two A. altamirensis strains isolated from the oxygen minimum zone (OMZ) water column and pleural fluid showing the absence of similarity of AAI with isolates from a specific matrix.…”
Section: A Altamirensis Isolation Identification and Characterizationmentioning
confidence: 65%
“…The absence of 16S rRNA and genomes related to A. altamirensis strains isolated from poultry does not allow the evaluation of its contamination route. of 4.1 Mb with a GC percentage of 64.99%, 4041 coding DNA sequences (CDS), and 3 16S rDNA, 1 23S rRNA, and 47 tRNA demonstrating characteristics comparable to other isolates of the same species [17]. The dendrogram tree (Figure 2) showed a high similarity between AAI and two A. altamirensis strains isolated from the oxygen minimum zone (OMZ) water column and pleural fluid showing the absence of similarity of AAI with isolates from a specific matrix.…”
Section: A Altamirensis Isolation Identification and Characterizationmentioning
confidence: 69%
See 2 more Smart Citations
“…This genus has previously been found in increased abundance in the leaf phyllosphere of ash trees tolerant to the fungal disease ash dieback, Hymenoscyphus fraxineus ( Ulrich et al., 2020 ). The inoculation of ash seedlings with Aureimonas altamirensis C2P003 had positive effect on the plant health and reduced ash dieback symptoms ( Becker et al., 2022 ). Furthermore, a study has shown an isolate of Aureimonas to have antifungal activity towards rice blast, Magnaporthe oryzae.…”
Section: Discussionmentioning
confidence: 99%